Debatable Diversity: Critical Dialogues on Change in American Universities - Padilla, Raymond V.,; Montiel, Miguel, (Rowman & Littlefield Publishers, 1998)
In this timely and thought-provoking book, the authors engage each other and the reader in an ongoing dialogue questioning the purpose and role of the contemporary university as bureaucratic, corporate, and diversified. Written as a series of conversations between the authors, two Chicano scholars at a western university, Debatable Diversity chronicles their own experiences as academic activists who struggled for decades to transform an American university system based more on entrepreneurship and the business model than on a dedication to the ideals set forth by a social awareness and support for civil rights that came out of the 1960s and early 1970s, a time when hope and faith in social change permeated college campuses. Instead, as Padilla and Montiel reveal, this commitment was never realized, and the lack of responsiveness of most American universities to the realities of shifting demographics and cultural diversity is the rule rather than the exception. Posing a challenge for all of those interested in transforming the university into a place that reflects the realities of the American cultural landscape, including growing minority populations, the challenge of maintaining a sense of humanity in the face of the information age, socioeconomic and class inequality, and the growing presence of minorities on campus, Debatable Diversity challenges readers to reexamine the purposes, goals, and functions of the American university in light of the ongoing social transformation from modernity to postmodernity. Not only do the authors offer an insider's look at the inner workings of academia, but also of academic activism, with the goal of renewal and reconfiguration of the contemporary 'multiversity.'